2018
DOI: 10.1002/jcp.26310
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of aquaporin 1 on aristolochic acid I induced epithelial mesenchymal transition on HK‐2 cells

Abstract: Aristolochic acid I (AA-I), one of the main active components in Aristolochaia herbs, may induce aristolochic acid nephropathy (AAN). Renal interstitial fibrosis is one of the most typical features of AAN. To investigate the mechanism of Aristolochic acid I (AA-I) -induced renal epithelial-mesenchymal transition (EMT) and determine the role of aquaporin-1 (AQP1) in this process, we established an AA-I-induced EMT model in human proximal tubular epithelial cells (HK-2 cells). Morphological examination, MTT assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…These findings overall suggest that loss of JAM-A promotes keratinocyte proliferation and migration, and the in vivo healing course, which is regulated by the signaling of FAK-mediated Erk1/2 activation. It is worthy to note that although the half-life of PF-562271 or PD98059 is not specified by the manufacturer, the working concentration and treatment duration regarding these two drugs are selected with great caution based on several important literatures 16 , 17 , 24 , 25 and our pilot experiments. The optimum concentration and treatment duration of JAM-A siRNA duplexes were also carefully selected based on our previously published works 26 and preliminary data, we found that transfection of keratinocytes with 100 nM JAM-A siRNA duplex (50 nM seq#1 + 50 nM seq#2, see Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings overall suggest that loss of JAM-A promotes keratinocyte proliferation and migration, and the in vivo healing course, which is regulated by the signaling of FAK-mediated Erk1/2 activation. It is worthy to note that although the half-life of PF-562271 or PD98059 is not specified by the manufacturer, the working concentration and treatment duration regarding these two drugs are selected with great caution based on several important literatures 16 , 17 , 24 , 25 and our pilot experiments. The optimum concentration and treatment duration of JAM-A siRNA duplexes were also carefully selected based on our previously published works 26 and preliminary data, we found that transfection of keratinocytes with 100 nM JAM-A siRNA duplex (50 nM seq#1 + 50 nM seq#2, see Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Next, JAM-A knockdown by RNAi was performed to investigate the regulative mechanism show JAM-A regulates keratinocyte proliferation and migration, as well as in vivo wound healing. Two drugs, PF-562271 and PD98059, were used to inhibit FAK activity 16 and Erk1/2 activity 17 , respectively. Our data demonstrate that the deficiency of JAM-A expression stimulated the proliferation and migration of human keratinocytes and improved the in vivo wound healing in rats, potentially through FAK/Erk signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Cells used for in vitro experiments were divided into three groups at 1x10 5 cells/well: Untreated group (control group), cells dosed with 10 µg/ml AAI (AAI group) and AAI cells treated with rapamycin (RMS; AAI + RMS). The dosage used was based on a previous study (17,18), which used 50 and 100 nM rapamycin for 24 h. Since no difference in morphology was found in cells treated with 50 and 100 nM AAI, 50 nM was used for subsequent experiments. Cells in the control group were grown in DMEM, while the AAI + RMS group was pre-treated with 50 and 100 nm rapamycin for 24 h. Cells in the AAI and treatment groups were dosed with 10 µg/ml AAI (Sigma Aldrich; Merck KGaA) for 24 h to induce injury.…”
Section: Methodsmentioning
confidence: 99%
“…When cells undergo EMT, cell adherence is attenuated and cell mobility is enhanced [15]. To investigate the effects of NDQ on cell movement in HK-2 cells, wound-healing assay was performed.…”
Section: Ndq Inhibits Cell Movement Migration and Invasion In Tgf-β1mentioning
confidence: 99%